Plan de negocio para la creación de la cooperativa de ahorro y crédito santa anita en la parroquia Mulliquindil del cantón Salcedo en el periodo 2013-2014 - Laica Lara, Jessica Paola (2015)
The present work is the result of a deep research that gives as a result the existence of the necessary conditions to run the creation of a credit union, to provide new services to benefit its members and partners, for which the proposal is intended to publicize the productive capacity of the company either through the size of the plant, equipment, and also will be the administrative culture of the company, detailing the general description of the product to get to know the needs that will be covered with each of the services to provide considering innovation of each one of them to reach the target market….